Effect of sediment depth, calcium hardness of water and feeding ration on nacre formation in freshwater mussel Lamellidens corrianus (Lea, 1834) - Hemchandra, N.; Dhaker, H. S.; Pathan, Dabir I.; Ghode, Gajanan (Indian Journal of Fisheries, 2015)
Survival and nacre formation was evaluated in freshwater mussel Lamellidens corrianus by varying sediment depth, calcium hardness of water and feeding ration. Different sediment depths (0, 3 and 6 cm), calcium hardness levels of water [(220.47 (T1), 282.63 (T2), 314.17 (T3) and 338.18 mg l-1 (T4)] and feeding rations [(1.5 x 106 (T1), 3.0 x 106 (T2) and (T3) 4.5 x 106 algal cells ml-1] were evaluated. Survival did not show significant difference while nacre formation was found to vary significantly (p